Waqf as a Solution in Solving the Problem of Poverty and Unemployment in Indonesia - Moh. Ihsan Fauzi; Iwan Ridhwani (Journal of Social Transformation and Regional Development, 2024)
The Poverty and unemployment are two main topics that are problems in the lives of people in various Muslim countries, especially Indonesia. On the other hand, Indonesia's large waqf assets and potential have not been fully managed properly for the welfare of the community. In fact, in some other countries, waqf can provide cheap and even free education and health services. This research aims to analyze waqf management as a solution in solving the problem of poverty and unemployment in Indonesia. This research uses qualitative methods with a literature review approach. The results of this study show that waqf is able to solve the problem of poverty and unemployment by managing waqf well and productively whose results and benefits are aimed at meeting the basic needs of the community such as clothing, food, house, education and health. Including using waqf as an investment that can open new jobs.